Evolution and structure of clinically relevant gene fusions in multiple myeloma - Steven M. Foltz (Nature Portfolio, 2020)
Multiple myeloma is characterised by frequent gene fusions. Here, the authors use data from the Multiple Myeloma Research Foundation CoMMpass Study to further investigate fusion genes in this disease and their clinical relevance.